2020
DOI: 10.1039/c9cc07821e
|View full text |Cite
|
Sign up to set email alerts
|

Donor–acceptor conjugated polymer-based nanoparticles for highly effective photoacoustic imaging and photothermal therapy in the NIR-II window

Abstract: BDA nanoparticles exhibit excellent theranostic properties including an extremely high cancer cell killing ability, admirable tumor elimination efficiency (100%) and a remarkable photoacoustic imaging contrast enhancing ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 25 publications
1
66
0
Order By: Relevance
“…The PD-FA nanoparticles displayed a broad absorption spectrum from the visible to NIR region. This indicated that for two characteristic peaks, at 450 nm and 845 nm, the former is mainly due to π-π* transition of the polymer backbone, 54 while the latter is ascribed to the optical absorption of PD-FA 2884 nanoparticles in NIR. With the broadband absorption spectrum, the PD-FA nanoparticles can satisfy different demands according to various requirements.…”
Section: Synthesis and Characterization Of The Pd-fa Nanoparticlesmentioning
confidence: 99%
“…The PD-FA nanoparticles displayed a broad absorption spectrum from the visible to NIR region. This indicated that for two characteristic peaks, at 450 nm and 845 nm, the former is mainly due to π-π* transition of the polymer backbone, 54 while the latter is ascribed to the optical absorption of PD-FA 2884 nanoparticles in NIR. With the broadband absorption spectrum, the PD-FA nanoparticles can satisfy different demands according to various requirements.…”
Section: Synthesis and Characterization Of The Pd-fa Nanoparticlesmentioning
confidence: 99%
“…Recently, a co ‐benzobisthiadiazole‐dithienosilole SP (SP34) with a maximum absorption peak at about 1090 nm was designed. [ 58 ] SP34 was coprecipitated with DSPE‐PEG to yield water‐soluble SPN34. The obtained SPN34 exhibited a superior photothermal conversion efficiency of 65% under NIR‐II laser irradiation and thus showed the powerful apoptosis/necrosis‐inducing ability for both in vitro and in vivo experiments.…”
Section: Nir‐ii Photothermal Therapymentioning
confidence: 99%
“…The polymer nanoparticles effectively inhibited or completely eradicate the liver tumors. Wei et al prepared a new type of narrow bandgap conjugated polymer-based near-infrared diagnostic nanoparticles with a photothermal conversion efficiency as high as 65% ( Wei et al, 2020 ). The obtained NPs PBBTDTS -Aptamer nanoparticles (BDA NPs) showed good ability to target to and accumulate in human liver cancer cells in vivo .…”
Section: Photothermal Treatmentmentioning
confidence: 99%